Aerobic training, but not creatine supplementation, alters the gluteus medius muscle - D'Angelis, F. H.F.; Ferraz, G. C.; Boleli, I. C.; Lacerda-Neto, J. C.; Queiroz-Neto, A. [UNESP] (Oxford University Press (OUP), 2005)
The aim of the present study was to investigate the effect of oral supplementation of creatine on the muscular responses to aerobic training. Twelve purebred Arabian horses were submitted to aerobic training for 90 d, with and without creatine supplementation, and evaluated with respect to BW and BCS and to the area and frequency of the different types of muscle fibers in the gluteus medius. Supplementation consisted of the daily administration of 75 g of creatine monohydrate mixed into the ration for the 90 d of training. Physical conditioning was conducted on a high-performance treadmill, and training intensity was stipulated by calculating the velocity at which blood lactate reaches 4 mmol/L, determined monthly for each animal. The individual intensity of physical force at 80% of aerobic threshold was established. Morphometry of gluteus medius muscle fibers was performed on frozen sections processed for histochemical analysis of myosin adenosine triphosphatase and immunohistochemistry of slow-contracting myosin. The results demonstrated that the animals maintained a moderate BCS without alteration of BW during the course of training, providing evidence of equilibrium between food intake and caloric expenditure during the study period. The present study demonstrated that aerobic training for 90 d caused hypertrophy of fiber types I (P = 0.04), IIA (P = 0.04), and IIX (P = 0.01), as well as an increase in the relative area occupied by type I fibers (P = 0.02) at the expense of type IIX fibers (P = 0.03), resulting in modifications of the contractile and metabolic characteristics of the gluteus medius muscle. It was not possible to show any beneficial effect from creatine on the skeletal muscle characteristics examined. ©2005 American Society of Animal Science. All rights reserved.
Keywords: Aerobic Training; Creatine; Gluteus Medius; Horses; Muscle Biopsy; Myosin ATPase